2014
DOI: 10.1155/2014/784056
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Outcomes between Early Fascial Closure and Delayed Abdominal Closure in Patients with Open Abdomen: A Systematic Review and Meta-Analysis

Abstract: Up to the present, the optimal time to close an open abdomen remains controversial. This study was designed to evaluate whether early fascial abdominal closure had advantages over delayed approach for open abdomen populations. Medline, Embase, and Cochrane Library were searched until April 2013. Search terms included “open abdomen,” “abdominal compartment syndrome,” “laparostomy,” “celiotomy,” “abdominal closure,” “primary,” “delayed,” “permanent,” “fascial closure,” and “definitive closure.” Open abdomen was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 53 publications
3
57
0
6
Order By: Relevance
“…A systematic review and meta-analysis to evaluate whether early fascial abdominal closure had advantages over delayed approach was published in 2014 [ 48 ]. Mortality, complications, and length of stay were compared between early and delayed fascial closure.…”
Section: Management Of Patients With Open Abdomenmentioning
confidence: 99%
“…A systematic review and meta-analysis to evaluate whether early fascial abdominal closure had advantages over delayed approach was published in 2014 [ 48 ]. Mortality, complications, and length of stay were compared between early and delayed fascial closure.…”
Section: Management Of Patients With Open Abdomenmentioning
confidence: 99%
“…44 Early fascial closure has been associated with improved outcomes for patients with the open abdomen. A metaanalysis 45 revealed lower mortality (P < .001) and fewer complications (P < .001) in patients in whom early fascial closure was achieved within 4 to 7 days of the initial laparotomy. IAP is monitored closely during and after the closure procedure.…”
Section: Closure Of the Open Abdomenmentioning
confidence: 99%
“…PFC is the most commonly primary outcome measure because it is reported to significantly reduce complication and mortality rates in the cases with early PFC, irrespectively of the technique for TAC (9). Although most systematic reviews reported preponderance of NPWT, the most recent meta-analysis of only comparative studies reported similar PFC rate in NPWT vs non-NPWT with significant heterogeneity between included studies (2).…”
Section: Primary Fascial Closurementioning
confidence: 99%